"Scandalous!": Reputation, impression management, and employee assistance programs (EAPs) in the NBA. Issue 4 (November 2015) - Agyemang, Kwame J.A.; Williams, Antonio S.; Kim, Dae Yeon
Abstract: This case study explores how the National Basketball Association (NBA) can rebuild its reputation in response to recurrent player scandals. The case centers on a reputation management firm that has been contracted by the league. The firm has been asked to develop programs that will permit players to make better decisions in their personal lives. NBA commissioner Adam Silver believes such programs will curb the likelihood of future player scandals, thereby enhancing the players' lives and limiting their ability to damage the league's reputation. To commence the process, the firm has been invited to sit-in on a meeting with Commissioner Silver and a group of NBA staff members who have past work experiences assisting players with their transition to the NBA. This reputation management case study is positioned in two key areas: impression management and employee assistance programs (EAPs). Upon reading the case, answering the provided questions, and completing the activities, students should come to a better understanding as to how to proactively manage corporate reputation. While fictitious names are given, the case study is based on actual interviews with current NBA staff members. The case is ideal for courses pertaining to strategy, policy, organizational behavior, and human resource management. The case could also be useful for sport marketing and sport finance courses if adapted to investigate how the created programs are important for branding and value.